Development of Integrated Learning Model Using Online Project-Based Learning to Enhance the System Thinking Ability for High-School Student - Phukongchai, Siriwanna; Teemuangsai, Sanit; Simmathan, Pawit (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purposes of this research were: 1. To study states, problems, and need assessment 2. to develop and 3. to study the effect of the Integrated learning Model Using Project-based Learning to Enhance the System Thinking Ability for High-School Student. This research was performed according to the research and development procedures into three phases. The sample there were 3 groups in the research; the first group consisted of 1,414 high school student and 650 teachers in academic year 2018; the second group was 7 specialists; and the target group was 33 in school. The research instruments were 1) Integrated lesson plans 2) Online project-based instruction 3) The behavior system thinking process measure. 4) The system thinking process measure. The statistics used for data were analyzed by using percentage, mean, standard deviation and t-test for dependent samples. The research revealed that 1) problems and needs assessment for integrated learning model using project-based learning to enhance the system thinking ability for high school students have expected in perception and needs assessment for the model using project-based learning in all aspects were at a high level, 2) development of integrated learning model included five factors and six steps, and 3) the testing scores after using the model was statistically higher than before using at the .05 level.